Update of the list of qualified presumption of safety (QPS) recommended microbiological agents intentionally added to food or feed as notified to EFSA 17: suitability of taxonomic units notified to EFSA until September 2022 - EFSA Panel on Biological Hazards (BIOHAZ); Konstantinos Koutsoumanis; Ana Allende; Avelino Alvarez‐Ordóñez; Declan Bolton; Sara Bover‐Cid; Marianne Chemaly; Alessandra De Cesare; Friederike Hilbert; Roland Lindqvist; Maarten Nauta; Luísa Peixe; et al. (EFSA Journal, 2023)
Abstract The qualified presumption of safety (QPS) approach was developed to provide a regularly updated generic pre‐evaluation of the safety of microorganisms, intended for use in the food or feed chains, to support the work of EFSA's Scientific Panels. The QPS approach is based on an assessment of published data for each agent, with respect to its taxonomic identity, the body of relevant knowledge and safety concerns. Safety concerns identified for a taxonomic unit (TU) are, where possible, confirmed at the species/strain or product level and reflected by ‘qualifications’. In the period covered by this Statement, new information was found leading to the withdrawal of the qualification ‘absence of aminoglycoside production ability’ for Bacillus velezensis. The qualification for Bacillus paralicheniformis was changed to ‘absence of bacitracin production ability’. For the other TUs, no new information was found that would change the status of previously recommended QPS TUs. Of 52 microorganisms notified to EFSA between April and September 2022 (inclusive), 48 were not evaluated because: 7 were filamentous fungi, 3 were Enterococcus faecium, 2 were Escherichia coli, 1 was Streptomyces spp., and 35 were taxonomic units (TUs) that already have a QPS status. The other four TUs notified within this period, and one notified previously as a different species, which was recently reclassified, were evaluated for the first time for a possible QPS status: Xanthobacter spp. could not be assessed because it was not identified to the species level; Geobacillus thermodenitrificans is recommended for QPS status with the qualification ‘absence of toxigenic activity’. Streptoccus oralis is not recommended for QPS status. Ogataea polymorpha is proposed for QPS status with the qualification ‘for production purposes only’. Lactiplantibacillus argentoratensis (new species) is included in the QPS list.